Case report: Immune-mediated meibomian gland dysfunction following pembrolizumab therapy for advanced urothelial carcinoma - Nguyen, Charles B.; Su, Christopher T.; Morgan, Meredith; Alva, Ajjai S. (Frontiers in Oncology, 2022)
Ocular immune-related adverse events are a relatively rare complication of immune checkpoint inhibitors. Common ocular toxicities range from dry eyes to inflammatory uveitis and ocular myasthenia gravis. Here, we present the case of a 55-year-old woman with recurrent urothelial carcinoma of the ureter after initially being managed with neoadjuvant cisplatin-based chemotherapy and surgical resection. She was treated with pembrolizumab which was complicated by immune-mediated pneumonitis after the eighth cycle, which was managed with a prolonged steroid course. The patient also developed red eyes along with recurrent styes. Eye examination revealed decreased tear breakup time, expression of thick and turbid meibum, and meibomian gland atrophy on infrared meibography. The patient was diagnosed with suspected immune-mediated meibomian gland dysfunction (MGD) as a result of pembrolizumab, a previously unreported complication of immunotherapy. The goal of MGD therapy is to stabilize the tear film and minimize evaporation with lipid-based lubricants and other conservative treatments.